2021
DOI: 10.1017/wtc.2021.6
|View full text |Cite
|
Sign up to set email alerts
|

Passive knee exoskeletons in functional tasks: Biomechanical effects of a SpringExo coil-spring on squats

Abstract: Passive wearable exoskeletons are desirable as they can provide assistance during user movements while still maintaining a simple and low-profile design. These can be useful in industrial tasks where an ergonomic device could aid in load lifting without inconveniencing them and reducing fatigue and stress in the lower limbs. The SpringExo is a coil-spring design that aids in knee extension. In this paper, we describe the muscle activation of the knee flexors and extensors from seven healthy participants during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Results indicated that an exoskeleton significantly reduced the required mechanical energy for tasks, which can help improve worker performance by reducing fatigue [ 6 ]. Based on a series of exoskeleton-based studies, researchers have demonstrated that this assistive-based technology improves both range of motion [ 16 , 17 ] and muscle fatigue or activation [ 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicated that an exoskeleton significantly reduced the required mechanical energy for tasks, which can help improve worker performance by reducing fatigue [ 6 ]. Based on a series of exoskeleton-based studies, researchers have demonstrated that this assistive-based technology improves both range of motion [ 16 , 17 ] and muscle fatigue or activation [ 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…As wearable technologies for industry advance in the realm of biomechanical task assessment, these systems will need to communicate through a layered data structure that integrates collected data throughout the workers’ environment to optimize performance and ensure worker health as a holistic system [ 46 ]. As smart factories continue to develop, advancements in industrial wearable devices will play an essential role in optimizing worker performance through those task components previously mentioned such as range of motion [ 16 , 17 ] and muscle fatigue or activation [ 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…It's important to understand how anthropometrics and fatigue affect the kinematics of the lower extremities during squats in order to create customised training plans and injury prevention techniques. Research into joint range of motion during squats based on stance width and anthropometrics, as well as studies into the effects of fatigue on lower extremity kinematics, offer important insights for improving training methods and reducing injury (Bengtsson et al, 2018;Escamilla, 2001;Escamilla et al, 2001;Hidayah et al, 2021;Milner et al, 2007) (Salem & Powers, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Given the assistant method of the passive exoskeleton, the elastic element has been used to assist human movement through combining the characteristics of human movement [31]. For example, Hidayah [32] used a coil-spring to assist knee extension. Walsh [19] designed a mechanical exoskeleton that has ankle and hip springs and a knee variable damper to bear a load.…”
Section: Introductionmentioning
confidence: 99%